HUBUNGAN ANTARA USIA MENARCHE DAN STATUS GIZI DENGAN SIKLUS MENSTRUASI REMAJA PUTRI DI MADRASAH ALIYAH AN-NAJAH KABUPATEN LOMBOK BARAT - Haryani; Zurriyatun Thoyibah; Sri Hardiani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Background: Menstruation is a natural process that occurs in every woman. Menstruation is periodic and cyclic bleeding from the uterus accompanied by the release (desquamation) of the endometrium. The ideal menstrual cycle is regular every month with a time span of 21-35 days for each menstrual period. Factors that can affect the menstrual cycle include age of menarche and nutritional status. Objective: This study aims to analyze the relationship between age of menarche and nutritional with the menstrual cycle. Method: This study used a quantitative cross-sectional design with 90 adolescent girls as respondents taken through a total sampling technique. Age of menarche was obtained through a questionnaire and nutritional status was measured based on body mass index (BMI) from weight and height data. Data analysis used the chi-square test. Results: There was a significant relationship between age of menarche (p = 0.001) and nutritional status (p = 0.035) with the menstrual cycle. Adolescents with menarche that occurs at an early age and poor or excessive nutritional status tend to experience irregular menstrual cycles. Conclusion: There is a significant relationship between age of menarche and nutritional status with the menstrual cycle.